Numerična analiza kazalnikov izkoristka nosilnosti cestnih vozil - Kolenc, Jurij (Strojniški vestnik, 2000)
There are numerous technical, technological and exploatation parameters for determining the transportation work efficiency of road vehicles, among the most important are the capacity-exploitation parameters. In this paper, the determination of static and dynamic coefficients of the capacity-exploitation parameters of road vehicles and their mutual comparison is analysed. A numerical analysis is realised for the case of one vehicle in one ride with cargo, for one vehicle in a defined time period, for a homogeneous motor pool or a group of vehicles with same capacity and an inhomogeneous motor pool or n groups of vehicles of the same benefit capacity.
Keywords: vozila cestna; nosilnost vozil; učinkovitost transporta; modeliranje numerično; transportna vozila; nosilnost